Reduction of transient soot emissions of a production Diesel engine using a fast soot sensor and closed loop control. Issue 5 (2019) - Meier, Florian; Schrangl, Patrick; Re, Luigi del
Abstract: Unfavorable combustion conditions during engine transient operation cause significantly higher emissions of toxic pollutants in comparison to static conditions. A closed loop controller could help to reduce these emissions under real driving conditions, provided the necessary measurements are available, in the diesel case mainly soot and NOx. In this paper we analyze the potential improvement of raw soot emissions using fast measurements. To this end, we consider the cumulated emissions obtained with the standard ECU setting and both with a new, fast Laser Induced Incandescence (LII) sensor and a production opacimeter. First, an emission model based on fast dynamic soot measurements is used to estimate the ideal tradeoff between soot and NOx. Then a feedback controller acting on the rail pressure is used to approximate the theoretical target. Experimental results confirm that a high reduction in soot can be achieved with a very low price in terms of NOx (-50%/+5%).